Vitamin D Signaling through Induction of Paneth Cell Defensins Maintains Gut Microbiota and Improves Metabolic Disorders and Hepatic Steatosis in Animal Models - Su, Danmei; Nie, Yuanyang; Zhu, Airu; Chen, Zishuo; Wu, Pengfei; Zhang, Li; Luo, Mei; Sun, Qun; Cai, Linbi; Lai, Yuchen; Xiao, Zhixiong; Duan, Zhongping; et al. (Frontiers in Physiology, 2016)
Metabolic syndrome (MetS), characterized as obesity, insulin resistance, and non-alcoholic fatty liver diseases (NAFLD)，is associated with vitamin D insufficiency/deficiency in epidemiological studies, while the underlying mechanism is poorly addressed. On the other hand, disorder of gut microbiota, namely dysbiosis, is known to cause MetS and NAFLD. It is also known that systemic inflammation blocks insulin signaling pathways, leading to insulin resistance and glucose intolerance, which are the driving force for hepatic steatosis. Vitamin D receptor (VDR) is highly expressed in the ileum of the small intestine，which prompted us to test a hypothesis that vitamin D signaling may determine the enterotype of gut microbiota through regulating the intestinal interface. Here, we demonstrate that high-fat-diet feeding (HFD) is necessary but not sufficient, while additional vitamin D deficiency (VDD) as a second hit is needed, to induce robust insulin resistance and fatty liver. Under the two hits (HFD+VDD), the Paneth cell-specific alpha-defensins including α-defensin 5 (DEFA5), MMP7 which activates the pro-defensins, as well as tight junction genes, and MUC2 are all suppressed in the ileum, resulting in mucosal collapse, increased gut permeability, dysbiosis, endotoxemia, systemic inflammation which underlie insulin resistance and hepatic steatosis. Moreover, under the vitamin D deficient high fat feeding (HFD+VDD), Helicobacter hepaticus, a known murine hepatic-pathogen, is substantially amplified in the ileum, while Akkermansia muciniphila, a beneficial symbiotic, is diminished. Likewise, the VD receptor (VDR) knockout mice exhibit similar phenotypes, showing down regulation of alpha-defensins and MMP7 in the ileum, increased Helicobacter hepaticus and suppressed Akkermansia muciniphila. Remarkably, oral administration of DEFA5 restored eubiosys, showing suppression of Helicobacter hepaticus and increase of Akkermansia muciniphila in association with resolving metabolic disorders and fatty liver in the HFD+VDD mice. An in vitro analysis showed that DEFA5 peptide could directly suppress Helicobacter hepaticus. Thus, the results of this study reveal critical roles of a vitamin D/VDR axis in optimal expression of defensins and tight junction genes in support of intestinal integrity and eubiosis to suppress NAFLD and metabolic disorders.